2020
DOI: 10.1002/spp2.1299
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships among bullhead sharks (Chondrichthyes, Heterodontiformes)

Abstract: The evolution of modern sharks, skates and rays (Elasmobranchii) is largely enigmatic due to their possession of a labile cartilaginous skeleton; consequently, taxonomic assignment often depends on isolated teeth. Bullhead sharks (Heterodontiformes) are a group of basal neoselachians, thus their remains and relationships are integral to understanding elasmobranch evolution. Herein we fully describe †Paracestracion danielia bullhead shark from the Late Jurassic plattenkalks of Eichst€ att, Germany (150-154 Ma)f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The placement of the pelvic and first dorsal fins suggests a slow swimming, epibenthic lifestyle [ 224 ]. Another important morphological feature of † Paracestracion is the presence of a root shelf on its teeth and the lack of development of molar teeth in juvenile specimens [ 59 ] and the lack of molariform teeth in pre-Kimmeridgian species [ 220 ].…”
Section: Taxonomic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The placement of the pelvic and first dorsal fins suggests a slow swimming, epibenthic lifestyle [ 224 ]. Another important morphological feature of † Paracestracion is the presence of a root shelf on its teeth and the lack of development of molar teeth in juvenile specimens [ 59 ] and the lack of molariform teeth in pre-Kimmeridgian species [ 220 ].…”
Section: Taxonomic Reviewmentioning
confidence: 99%
“…However, Hovestadt [ 226 ] considers this species to be a nomen nudum , because the specimen lacks the dentition completely. In a more recent study, Slater et al [ 59 ] nevertheless identified this species as belonging to Heterodontus based on the position of the pelvic girdles between the dorsal fins ( Figure 20B–D ). Pending further revisions of all Late Jurassic heterodontiforms based on skeletal material might provide a better understanding of their taxonomic composition.…”
Section: Taxonomic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…-Sharks: René Kindlimann, in Klug and Bolliger 2012;Mollen et al 2012;Kriwet et al 2015;Pollerspöck et al 2018;Jambura et al 2018Jambura et al , 2019Bracher et al 2019;Stumpf et al 2019;Slater et al 2020;…”
Section: Amateur Palaeontologists/citizen Scientists/ Private Collectorsunclassified